A Meta Analysis–Tridoshaj Sarvasara Mukhapaka Vis-À-Vis Oral Submucous Fibrosis - Sharma, Aparna; Kumar, Ashok; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2022)
Oral Submucous Fibrosis (OSMF) is a chronic disease characterized by the deposition of the abnormal collagen. It is a pre-malignant condition in approximately 2% of the cases. Ayurveda mentions a few matching conditions as Tridoshaj Sarvasara Mukhapaka & suggests various treatment modalities; local therapies as Gandusha & systemic ones as consumption of Rasayana, Tridoshaghna herbs & herbals, along with Nidana Parivarjana / Abstinence from addictions. This article reviews various aspects as literary & clinical studies pertaining to OSMF / Tridoshaj Sarvasara Mukhapaka as per the modern medicine, including prevention, Surgery, diet, lifestyle, physiotherapy, Ayurveda with other Complementary Alternative Medicines are reviewed here.